Hypersensitivity Test of Insect-Carried Bacteria in Chilli Crop at Banyumas Regency - Agus Suroto; Endang Mugiastuti; Tarjoko Tarjoko; Eka Oktaviani; Muhammad Bahrudin (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2023)
As a horticultural crop with high economic and cultural values, the productivity of chili (Capsicum annum L.) fluctuates from time to time. This is influenced by changes in weather and climate which lead to the low resistance of chili plants to pests and diseases. Climate change can affect the existence of pests and diseases in plants and even reduce yields between 10-28% on a global scale. Bacteria, in association with plants, can be both pathogenic and non-pathogenic. While pests tend to have a negative relationship with plants because they can cause damage to plants. Banyumas Regency (Central Java) is one of the districts that contribute to the supply of chili which is important to increase production. This study aims to distinguish pathogenic and non-pathogenic bacteria, which are carried by insects in chili planting fields in 3 (three) endemic locations for pest attacks, namely Sumbang, Sokaraja, and Karanglewas Districts. The research was conducted from March to November 2021. As many as 83.33% of the total grown isolates did not show hypersensitive reactions while the others showed positive results. However, further research needs to be carried out for further research (characterization, identification, and other potential of the isolated insect-borne bacteria).